The Protective Effects of Insulin and Natural Honey against Hippocampal Cell Death in Streptozotocin-Induced Diabetic Rats - Iraj Jafari Anarkooli; Hossein Barzegar Ganji; Maryam Pourheidar (Journal of Diabetes Research)
We investigated the effects of insulin and honey as antioxidants to prevent the hippocampal cell death in streptozotocin-induced diabetic rats. We selected sixty Wister rats (5 groups of 12 animals each), including the control group (C), and four diabetic groups (control (D) and 3 groups treated with insulin (I), honey (H), and insulin plus honey (I + H)). Diabetes was induced by streptozotocin injection (IP, 60 mg/kg). Six weeks after the induction of diabetes, the group I received insulin (3-4 U/kg/day, SC), group H received honey (5 mg/kg/day, IP), and group I + H received a combination of the above at the same dose. Groups C and D received normal saline. Two weeks after treatment, rats were sacrificed and the hippocampus was extracted. Neuronal cell death in the hippocampal region was examined using trypan blue assay, “H & E” staining, and TUNEL assay. Cell viability assessment showed significantly lower number of living cells in group D than in group C. Besides, the mean number of living cells was significantly higher in group I, H, and I + H compared to group D. Therefore, it can be concluded that the treatment of the diabetic rats with insulin, honey, and a combination of insulin and honey can prevent neuronal cell death in different hippocampal areas of the studied samples.